Briefs and beyond : persuasive legal writing - Beazley, Mary Beth; Smith, Monte G. (New York : Wolters Kluwer, 2021)
"Law school book for courses on persuasive or advanced legal writing"-- Provided by publisher
Keywords: Forensic orations; Forensic orations United States; Legal briefs; Legal composition